A community-based lifestyle and weight loss intervention promoting a Mediterranean-style diet pattern evaluated in the stroke belt of North Carolina: the Heart Healthy Lenoir Project. (December 2016) - Keyserling, Thomas; Samuel-Hodge, Carmen; Pitts, Stephanie; Garcia, Beverly; Johnston, Larry; Gizlice, Ziya; Miller, Cassandra; Braxton, Danielle; Evenson, Kelly; Smith, Janice; Davis, Gwen; Quenum, Emmanuelle; et al.
Abstract Background Because residents of the southeastern United States experience disproportionally high rates of cardiovascular disease (CVD), it is important to develop effective lifestyle interventions for this population. Methods The primary objective was to develop and evaluate a dietary, physical activity (PA) and weight loss intervention for residents of the southeastern US. The intervention, given in eastern North Carolina, was evaluated in a 2 year prospective cohort study with an embedded randomized controlled trial (RCT) of a weight loss maintenance intervention. The intervention included: Phase I (months 1–6), individually-tailored intervention promoting a Mediterranean-style dietary pattern and increased walking; Phase II (months 7–12), option of a 16-week weight loss intervention for those with BMI ≥ 25 kg/m2 offered in 2 formats (16 weekly group sessions or 5 group sessions and 10 phone calls) or a lifestyle maintenance intervention; and Phase III (months 13–24), weight loss maintenance RCT for those losing ≥ 8 lb with all other participants receiving a lifestyle maintenance intervention. Change in diet and PA behaviors, CVD risk factors, and weight were assessed at 6, 12, and 24 month follow-up. Results Baseline characteristics (N  = 339) were: 260 (77 %) females, 219 (65 %) African Americans, mean age 56 years, and mean body mass index 36 kg/m2 . In Phase I, among 251 (74 %) that returned for 6 month follow-up, there were substantial improvements in diet score (4.3 units [95 % CI 3.7 to 5.0]), walking (64 min/week [19 to 109]), and systolic blood pressure (−6.4 mmHg [−8.7 to −4.1]) that were generally maintained through 24 month follow-up. In Phase II, 138 (57 group only, 81 group/phone) chose the weight loss intervention and at 12 months, weight change was: −3.1 kg (−4.9 to −1.3) for group (N  = 50) and −2.1 kg (−3.2 to −1.0) for group/phone combination (N  = 75). In Phase III, 27 participants took part in the RCT. At 24 months, weight loss was −2.1 kg (−4.3 to 0.0) for group (N  = 51) and −1.1 kg (−2.7 to 0.4) for combination (N  = 72). Outcomes for African American and whites were similar. Conclusions The intervention yielded substantial improvement in diet, PA, and blood pressure, but weight loss was modest. Trial registration clinicaltrials.gov Identifier:NCT01433484